2017
DOI: 10.1371/journal.pone.0180937
|View full text |Cite
|
Sign up to set email alerts
|

Defining and characterizing the critical transition state prior to the type 2 diabetes disease

Abstract: BackgroundType 2 diabetes mellitus (T2DM), with increased risk of serious long-term complications, currently represents 8.3% of the adult population. We hypothesized that a critical transition state prior to the new onset T2DM can be revealed through the longitudinal electronic medical record (EMR) analysis.MethodWe applied the transition-based network entropy methodology which previously identified a dynamic driver network (DDN) underlying the critical T2DM transition at the tissue molecular biological level.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
0
15
0
4
Order By: Relevance
“…The proposed evidence-based 4-stage model outlined below emphasizes the context of prediabetes as a component in the progression of DBCD, with opportunities for various prevention modalities to reduce evolution to T2D, CVD, or both ( Fig. 1 (118). Along these lines, Khera et al (119) found that in patients with a high genetic (molecular) risk for coronary heart disease, a favorable (healthy) lifestyle was associated with a nearly 50% reduction in relative risk.…”
Section: The Specific Context Of Dbcd As the Insulin Resistance-predimentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed evidence-based 4-stage model outlined below emphasizes the context of prediabetes as a component in the progression of DBCD, with opportunities for various prevention modalities to reduce evolution to T2D, CVD, or both ( Fig. 1 (118). Along these lines, Khera et al (119) found that in patients with a high genetic (molecular) risk for coronary heart disease, a favorable (healthy) lifestyle was associated with a nearly 50% reduction in relative risk.…”
Section: The Specific Context Of Dbcd As the Insulin Resistance-predimentioning
confidence: 99%
“…Those with insulin resistance are at higher risk of progressing along the DBCD continuum and merit primary disease prevention: structured lifestyle interventions that reduce cardiometabolic risk factors and later DBCD stage likelihoods, respectively. A molecular roadmap for this process was recently presented by Jin et al(118), who identified a dynamic driver network governing the key predisease-T2D transition mechanisms. It is postulated that appropriate interventions (such as structured lifestyle change) at these critical time points could prevent or delay progression of disease…”
mentioning
confidence: 99%
“…Adipocytes are cells that form and store lipids in adipose tissue, they play a major role in energy homeostasis [1,2]. Obesity, which is characterized by increased storage of lipids in adipose tissue and modification of the metabolic functions of adipocytes, is a risk factor for several metabolic diseases, including atherosclerosis, cardiovascular ischemic disease, hypertension, hyperglycemia and insulin resistance in type 2 diabetes [1,3,4,5,6,7]. The molecular composition of adipose tissue may reveal its functionality and links to metabolic disease [8,2].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the analogy between phase transitions occurring in living systems (such as normal to diseased state transition) and physical systems (such as condensation of water) has been well-motivated (Davies et al 2011;Holstein et al 2013;Trefois et al 2015;Smith 2010). The normal state to cancer state transition has been described as a process similar to the first-order irreversible discontinuous phase transition occurring in physical systems (Facciotti 2013;Jin et al 2017;Liu et al 2013;Mojtahedi et al 2016;Torquato 2010). The central idea is that living systems are open systems in quasisteady state type equilibrium in continuous exchange with their environment wherein cells behave like a network in heat bath under external perturbations (Pastor-Satorras et al 2015;Scheffer et al 2012).…”
Section: Introductionmentioning
confidence: 99%